La adopción de nuevas variedades de frijol en Costa Rica: logros y desafíos - Pachico, Douglas H.; Borbón Castro, E. (International Center for Tropical Agriculture, 1986)
Results of a survey of 159 farmers in southern Costa Rica indicate that the new bean varieties Talamanca and Brunca are widely adopted. This report analyzes the factors determining their success. The role played by seed availability is considered. Farmers evaluated these varieties in terms of yield, plant architecture, and disease tolerance. Adoption was greater in the planted system than in the covered system. The economic analysis of both systems attempted to determine why the planted system is displacing the covered system by examining land use and costs and returns of the two production systems. The covered bean system is used more by large-scale farmers, whereas the planted system is relatively more important among small farmers